A Proteção da Natureza e do Patrimônio da Humanidade pela Beleza Cênica da Paisagem - Lucimar de Fátima dos Santos Vieira; Roberto Verdum (Confins)
When landscapes began to awaken in human societies the need for their protection? What is the significance and importance of the scenic beauties of the landscape? Why are scenic beauties protected in legislation? This article aims to explain when, how and why landscapes began to awaken in human society the need for protection, especially their scenic beauty, because environmental protection is the object of concern, to a greater or lesser extent, of all peoples. It begins with the presentation of the trajectory of construction of the concept of heritage and historical and natural monument, about the organization of civil society and the creation of international organizations to promote protection through legal instruments and also the creation of areas protected, marked by nationalist sentiment and, later, by an internationalist vision in a historical, political, social, economic and scientific context.